Study on Amyotrophic lateral Sclerosis: A Disease of Motor Neuron in Pakistan - Daud, Shakeela (International Journal of Pathology, 2022)
This review describes the most common motor neuron disease, amyotrophic lateral sclerosis (ALS). Motor neuron disease (MND) is a neurodegenerative condition affecting the brain and spinal cord. Motor neurons transmit messages from brain to spinal cord and then muscles. It is considered by the deterioration of mostly motor neurons, leading to muscle weakness. Patients with amyotrophic lateral sclerosis is the most common type of the MNDs, showing equally pure upper and lower motor neurons symptoms, such as hyperreflexia, spasticity, extensive plantar signs and progressive muscular weakness, fasciculation, and atrophy causing fatal paralysis. ALS is occurring in 1.7 2.3 out of 100,000 patients worldwide. ALS can be broadly categorized into familial and sporadic while in familial form of ALS approximately 10-20% are due to genetic factors. Epidemiological studies have proposed that ALS patients have been exposed to environmental factors such as exposure to agriculture, chemicals, solvents, heavy metals, electrical meadows. The most familiar genetic cause of ALS is mutations in Cu/Zn ions Super Oxide Dismutase 1. ALS disease commonly attacks between age 40 and 60. More men develop it than women. The diagnosis remains clinical with diagnostic support. Other diagnoses can generally be ruled out with the help of neuroimaging studies. Paralysis is advanced and goes to death due to respiratory failure in about 3–5 years after onset of disease... There is no cure. Medicines can relieve symptoms of ALS and sometimes, prolong survival of this disease.